Molecular analysis demonstrates high prevalence of chloroquine resistance but no evidence of artemisinin resistance in Plasmodium falciparum in the Chittagong Hill Tracts of Bangladesh - Alam, Mohammad Shafiul (Malar J, 2017)
BACKGROUND: Artemisinin resistance is present in the Greater Mekong region and poses a significant threat for current anti-malarial treatment guidelines in Bangladesh. The aim of this molecular study was to assess the current status of drug resistance in the Chittagong Hill Tracts of Bangladesh near the Myanmar border. METHODS: Samples were obtained from patients enrolled into a Clinical Trial (NCT02389374) conducted in Alikadam, Bandarban between August 2014 and January 2015. Plasmodium falciparum infections were confirmed by PCR and all P. falciparum positive isolates genotyped for the pfcrt K76T and pfmdr1 N86Y markers. The propeller region of the kelch 13 (k13) gene was sequenced from isolates from patients with delayed parasite clearance. RESULTS: In total, 130 P. falciparum isolates were available for analysis. The pfcrt mutation K76T, associated with chloroquine resistance was found in 81.5% (106/130) of cases and the pfmdr1 mutation N86Y in 13.9% (18/130) cases. No single nucleotide polymorphisms were observed in the k13 propeller region. CONCLUSION: This study provides molecular evidence for the ongoing presence of chloroquine resistant P. falciparum in Bangladesh, but no evidence of mutations in the k13 propeller domain associated with artemisinin resistance. Monitoring for artemisinin susceptibility in Bangladesh is needed to ensure early detection and containment emerging anti-malarial resistance.